PENGARUH KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN LABORATORIUM DAN BAGIAN PRODUKSI PT BANUA LIMASEJURUS BANJARMASIN - Mailiana Mailiana; Diana Hayati; Alvin Halim (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
This research aims to determine the effect of work safety on the performance of employees in the laboratory and production divisions of PT Banua LimaSejurus Banjarmasin partially and simultaneously. The subjects in this study were employees of the laboratory and production divisions, totaling 85 people. The method used in this study was a quantitative analytical method, which provided empirical evidence of the effect of work safety on the performance of employees in the laboratory and production divisions at PT Banua Limasejurus Banjarmasin. This study uses numbers as research data with the independent variable is work safety (X) and the dependent variable is employee performance (Y). The results of the study prove that the work safety variables have a partial effect on the performance of employees in the laboratory and production divisions at PT Banua Limasejurus Banjarmasin. Variable The existence of a manual for the use of tools and or danger signs (X2) has the most dominant effect on the performance of employees in the laboratory and production divisions at PT Banua Limasejurus Banjarmasin.